Analisis Kandungan Besi pada Air Tanah Bansir Darat Pontianak Tenggara - Rachmat Sahputra (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2021)
Abstract: The difficulty in getting clean water from the residents of Southeast Pontianak's Bansir Darat requires information regarding the iron content are contained in wells in the area. Determination of iron content using the Atomic Absorption Spectophotometer (AAS) method is based on the atomization of iron compounds in solution in a low pH (pH 2-5). The iron compound will be atomized with flame on AAS to produce emission rays that produce a wavelength of 248.3 nm for Fe which is captured by the detector which is then digitally converted to produce iron content by comparing it with the appropriate iron standard series in the sample content range, 0.00; 0.20; 0.80; 1,2; and 1.6 mg / L Fe. The results of the analysis show that the depth of the well in the Southeast Pontianak area of Bansir Darat resulted in differences in iron content. For shallow wells 3 m have a content of 0.91 mg/L, while wells with a depth of 22 m show an iron content of 0.09 mg / L. The deeper the well is from the ground, the iron content is lower than the shallow well.Keywords: Analysis of iron content, well water, AAS, Bansir Darat of Southeast PontianakAbstrak: Kesulitan air bersih dari warga Bansir Darat Pontianak Tenggara, memerlukan informasi terkait kandungan besi yang terkandung dalam sumur-sumur di wilayah tersebut. Penentuan kandungan besi menggunakan metoda Atomic Absorption Spectofotometer (AAS) berdasarkan pada atomisasi dari senyawa besi dalam larutan dalam suasana pH rendah pH 2-5. Senyawa besi akan teratomisasi dengan Nyala pada AAS menghasilkan sinar emisi yang menghasilkan panjang gelombang 248,3 nm untuk Fe yang ditangkap detektor yang selajutnya dikonversi secara digital menghasilkan kandungan besi dengan membandingkan dengan deret standar besi yang sesuai dalam range kandungan sampel yaitu 0,00; 0,20; 0,80; 1,2; dan 1,6 mg/L Fe. Hasil analisis menunjukkan bahwa kedalaman sumur di wilayah Bansir Darat Pontianak Tenggara menghasilkan perbedaan kandungan besi. Untuk sumur dangkal 3 m memiliki kandungan 0,91 mg/L, sedangkan sumur dengan kedalaman 22 m menunjukkan hasil kandungan besi 0,09 mg/L. Semakin dalam sumur dari permukaan tanah kandungan besinya lebih rendah daripada sumur yang dangkal.Kata-kata kunci: Analisis kandungan besi, air sumur, ASS, Bansir Darat Pontianak Tenggara